2011
DOI: 10.1242/dev.061036
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis repressor of light signaling SPA1 acts in the phloem to regulate seedling de-etiolation, leaf expansion and flowering time

Abstract: Plants adjust their growth and development in response to the ambient light environment. These light responses involve systemic signals that coordinate differentiation of different tissues and organs. Here, we have investigated the function of the key repressor of photomorphogenesis SPA1 in different tissues of the plant by expressing GUS-SPA1 under the control of tissue-specific promoters in a spa mutant background. We show that SPA1 expression in the phloem vasculature is sufficient to rescue the spa1 mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 64 publications
2
38
0
Order By: Relevance
“…This latter finding is in agreement with our results showing that flowering time regulation by R:FR does not require COP1/SPA. Moreover, SPA proteins and phyB act in distinct tissues in the control of flowering time: while phyB acts in the mesophyll, SPA1 acts in the phloem (Endo et al, 2005;Ranjan et al, 2011). Previous results have shown that white light + FR increases CO transcript levels and also enhances CO protein stability .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This latter finding is in agreement with our results showing that flowering time regulation by R:FR does not require COP1/SPA. Moreover, SPA proteins and phyB act in distinct tissues in the control of flowering time: while phyB acts in the mesophyll, SPA1 acts in the phloem (Endo et al, 2005;Ranjan et al, 2011). Previous results have shown that white light + FR increases CO transcript levels and also enhances CO protein stability .…”
Section: Discussionmentioning
confidence: 97%
“…This was necessary to allow DR5::GUS detection. Seedlings were then either kept in high R:FR or shifted to low R:FR for 7 h. They were incubated in GUS staining buffer (Ranjan et al, 2011), but without vacuum infiltration, at 37掳C for 16 h in darkness and subsequently destained in 70% ethanol.…”
Section: Histochemical Analysis Of Gus Activitymentioning
confidence: 99%
“…The observed GA 3 -Fl broader distribution throughout the leaf might be directly related to normal TEM repression of GA biosynthesis in the leaf mesophyll structure and/or due to an effect on GA transport. To further support this, we first cloned an artificial microRNA (amiRNA), previously used for partial silencing of both TEM genes (Osnato et al, 2012), under the mesophyll-specific CHLOROPHYLL A/B BINDING PROTEIN 3 promoter (PCAB3; Endo et al, 2007;Ranjan et al, 2011). Transgenic plants expressing amiRTEM under the mesophyll-specific PCAB3 promoter, showed similar GA 3 -Fl accumulation patterns to tem1-1 tem2-2.…”
Section: Tem1 and Tem2 Repress Trichome Initiation In Leaves And Inflmentioning
confidence: 99%
“…To test the effect of reducing GA levels in specific tissues, GA2ox7 cDNA was fused to promoters with specific expression patterns that have been used previously to misexpress regulatory proteins Ranjan et al, 2011). The KNAT1 promoter, which is active in the shoot apical meristem, and the SUC2 promoter, which is specific to the companion cells of the phloem, were used.…”
Section: Misexpression Of Ga2ox7 In Different Tissues Causes Ga Deficmentioning
confidence: 99%